Direct analysis in real time coupled with dried spot sampling for bioanalysis in a drug-discovery setting. (June 2011) - Crawford, Elizabeth; Gordon, Justin; Wu, Jing-Tao; Musselman, Brian; Liu, Ray; Yu, Shaoxia
Background: Conventional mouse or rat pharmacokinetic/toxicokinetic (PK/TK) studies frequently require sacrifice or use of multiple animals for a full time-course in order to obtain adequate blood volume. Currently accepted LC––MS/MS analyses require tedious sample preparation and large blood volume, therefore, a bioanalytical method with a simpler blood-sampling procedure using fewer animals, lower sample volume and no additional sample preparation is desirable.Results: We have developed a method that combines the direct analysis in real time (DART) open-air ambient ionization source and MS/MS to directly analyze dried blood spots (DBS) on glass from low volume whole blood samples without additional sample preparation or manipulation of the spots. Single mouse serial bleeding was performed for sample collection for DART-MS/MS and the results were comparable to the conventional terminal bleeding method for LC––MS/MS.Conclusion: The DART-MS/MS method was applied to DBS sampling for PK/TK studies and also for in vitro screening of absorption, distribution, metabolism and excretion properties. The results from the DART-MS/MS approach correlated well with the LC––MS/MS analyses for comparison.